CHARACTERISTICS OF THE CLINICAL PATHOGENETIC COURSE OF RECURRENT BRONCHITIS IN CHILDREN ON THE BACKGROUND OF COMORBID DISEASES - Achilova Donokhan Nutfullaevna; Ochilova Dilrabo Komil qizi (Web of Journals Publishing, 2025)
This article analyzes the clinical and pathogenetic course of recurrent bronchitis in children against the background of comorbid diseases. Also, the mechanism of development, diagnosis and treatment methods are discussed in this case.
Keywords: children, recurrent bronchitis, comorbid diseases, pathogenesis, immunological changes.